Analysis of Lesson Plans for Teaching Speaking - Ida Farida (English Education Journal, 2018)
This study was done to find out the appropriateness of the English lesson plans developed by the two English teachers for the eleventh grade senior high school (SMA) students in the first semester based on the 2013 Curriculum and to investigate the process of teaching speaking based on those lesson plans at SMA Negeri 1 Meulaboh. This study employed a descriptive qualitative method using  observation sheets, an interview guide, and study of documents to collect the data. Two lesson plans were analyzed based on six meeting observations. The data was analyzed through the processes of data reduction, data display, and drawing conclusions. The findings showed that the lesson plans developed by the teachers were appropriate with the 2013 Curriculum. Specifically, all of the components of the lesson plan such as core competence, basic competence and indicators of competency achievement, objectives, materials, methods of teaching, media, resources, teaching activities, and methods of assessment were covered in the lesson plans developed. However, there were some crucial deficiencies found in some components, such as the materials developed did not completely cover language elements; the resources planned in the lesson plan were not varied; and there was no motivation included in the pre-teaching activities. Meanwhile, the teaching activities presented in the classroom were based on what had been stated in the lesson plans. The three stages of the activities, namely pre-teaching, while-teaching and post-teaching activities described the teaching-learning processes for the lessons in speaking English in the classroom.